2022
DOI: 10.3389/fmolb.2022.867303
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer-Promoter Communication: It’s Not Just About Contact

Abstract: Cis-regulatory elements such as enhancers can be located even a million base pairs away from their cognate promoter and yet modulate gene transcription. Indeed, the 3D organisation of chromatin enables the establishment of long-range enhancer-promoter communication. The observation of long-range enhancer-promoter chromatin loops at active genes originally led to a model in which enhancers and promoters form physical contacts between each other to control transcription. Yet, recent microscopy data has challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 92 publications
(127 reference statements)
1
3
0
Order By: Relevance
“…Interestingly, a recent study using human primary cells showed VPA promoted both histone acetylation and deacetylation, and the increase in histone acetylation with VPA is regional 23 . The increase in gene expression with VPA as we observed in our glioma cell lines may be driven by alternate promoters 24 or complex interaction between promoter and enhancers 25 .…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly, a recent study using human primary cells showed VPA promoted both histone acetylation and deacetylation, and the increase in histone acetylation with VPA is regional 23 . The increase in gene expression with VPA as we observed in our glioma cell lines may be driven by alternate promoters 24 or complex interaction between promoter and enhancers 25 .…”
Section: Discussionsupporting
confidence: 51%
“…The transfer of activating signals from distal enhancers to promoters typically (though not always) depends on connections between these elements within the nucleus. These connections can be established through direct 3D chromosomal contacts or potentially through other mechanisms, such as phase separation [3][4][5][6] . Previous studies that compared the dynamics of enhancer activation, enhancer-promoter connections and gene expression across cell types and conditions have found that these events are often correlated, although cases whereby enhancerpromoter contacts precede enhancer activation and gene induction are also common 4,[7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…These points represent ‘loops’, and may manifest individually or as components of grids, often found at domain corners. Accordingly, chromatin loops are considered the primary mechanism of enhancer-promoter interactions facilitated upon cohesin-mediated loop extrusion accompanied with barrier elements [45,46,47]. A chromatin loop consists of a pair of proximal regions, referred as loop anchors.…”
Section: Resultsmentioning
confidence: 99%